Assessment of the REPLACE study composite endpoint in riociguat-treated patients in the PATENT study. (December 2020) - Simonneau, Gérald; Ghofrani, Hossein-Ardeschir; Corris, Paul A.; Rosenkranz, Stephan; Grünig, Ekkehard; White, Jim; McLaughlin, Vallerie V.; Langleben, David; Meier, Christian; Busse, Dennis; Kleinjung, Frank; Benza, Raymond L.
The goal of treatment in patients with pulmonary arterial hypertension is to achieve a low risk status, indicating a favorable long-term outcome. The REPLACE study investigated the efficacy of switching to riociguat in patients with pulmonary arterial hypertension and an insufficient response to phosphodiesterase-5 inhibitors. In this post hoc analysis, we applied the REPLACE composite endpoint of clinical improvement to the placebo-controlled PATENT-1 study of riociguat in pulmonary arterial hypertension and its long-term extension, PATENT-2. Clinical improvement was defined as ≥2 of the following in patients who completed the study without clinical worsening: ≥10% or ≥30 m improvement in 6-minute walking distance; World Health Organization functional class I or II; ≥30% decrease in N -terminal prohormone of brain natriuretic peptide. At PATENT-1 Week 12, patients treated with riociguat were more likely to achieve the composite endpoint vs. placebo ( P < 0.0001), with similar results in pretreated ( P = 0.0189) and treatment-naïve ( P < 0.0001) patients. Achievement of the composite endpoint at Week 12 was associated with a 45% reduction in relative risk of death and a 19% reduction in relative risk of clinical worsening in PATENT-2. Overall, these data suggest that use of the REPLACE composite endpoint in patients with pulmonary arterial hypertension is a valid assessment of response to treatment.